Duck circovirus induces a new pathogenetic characteristic, primary sclerosing cholangitis. (April 2019) - Zhu, Dongjin; Zhou, Defang; Liu, Jie; Hao, Xiaojing; Cheng, Ziqiang
Highlights: DuCV induces primary sclerosing cholangitis (PSC) in natural and reproductive duck cases. DuCV shows high tropism to epithelial cell of bile duct. The pathology model of PSC that induced by DuCV sheds light on mechanism of PSC study. Abstract: Primary sclerosing cholangitis (PSC) is a chronic, cholestatic liver disease of unknown cause. In the study, we found that duck circovirus (DuCV) induces PSC in natural and reproductive cases. PSC in DuCV naturally infected ducks was investigated by PCR and histopathology. A model of PSC was developed in one-day old duck by infection of DuCV. Effects on serum levels of liver enzymes and histology were evaluated, and DuCV tropism for bile duct in liver was analyzed by immuohistochemistry. Pathology observation of natural or reproductive DuCV infected ducks showed that the lesion of liver were characterized by cholangiocytic injuries and progressive fibrous obliteration of the biliary tree associated with lymphocytes infiltration. ALT, AST, ALP, GGT, ALB, TBIL and TP were significantly increased in serum of DuCV infected ducks. DuCV showed higher tropism for epithelial cells of bile duct than other cells in PSC.